CLINICOPATHOLOGICAL STUDY OF BREAST CANCER AND IMMUNOHISTOCHEMICAL EXPRESSION OF BRCA 1 AND BRCA2 – A PROSPECTIVE STUDY - perugu, naveen chand; komanapalli, sunilkumar; kuna, rajani; CHOWDARI, BALAJI; DEVI, URMILA; das, Basumitra (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of this study was to study morphological features of breast cancer (BRCA), to grade according to Nottingham’s modification of Bloom Richardson (BR) grading system and to detect the immunohistochemical (IHC) expression of BRCA 1 and BRCA 2 proteins among the clinicopathological parameters of BRCA as age, menopausal status, tumor size, histopathological grade, and lymphnode status. Methods: This is a prospective and observational study conducted in the Department of Pathology from January 2015 to October 2016, Histopathological examination of 79 cases of Breast carcinoma was conducted and IHC using BRCA 1 and BRCA2 was done in 40 cases. Results: Out of 79 invasive breast carcinoma, the most common age group for breast carcinoma was 40–49 (40.5%) years. The most common histological subtype was invasive carcinoma-NST, 77(97.4%) cases. Forty cases studied for both BRCA-1 and BRCA 2 expression, regarding BRCA-1 expression, 11 cases showed score 1, 19 cases were of score 2, and eight cases belonged to score 3. Two cases did not show any expression. A positive statistical correlation existed between the size of the tumor, modified BR grade of tumor with BRCA-1 expression. Regarding BRCA-2 expression, 12 cases showed score 1, 17 cases was of score 2, and 10 cases belonged to score 3. One case did not show any expression. Conclusion: BRCA gene participates in the pathogenesis of breast carcinomas. It is an indicator of poor prognosis. BRCA positivity decreased with increase in age, size of tumor, lymphnodes showing metastasis, and higher grade of the tumor. The present study indicates that BRCA is a powerful predictor of prognosis.